Global and regional myocardial function quantification in takotsubo cardiomyopathy in comparison to acute anterior myocardial infarction using two-dimensional (2D) strain echocardiography - Heggemann, Felix; Hamm, Karsten; Kälsch, Thorsten; Süselbeck, Tim; Papavassiliu, Theano; Borggrefe, Martin; Haghi, Dariusch (Echocardiography, 2011)
Aims: This study sought to compare global and regional myocardial function in Takotsubo cardiomyopathy (TC) to that in acute anterior myocardial infarction (AMI) using 2D strain imaging. Methods: Twelve consecutive patients with TC (ten women, two men) and 12 patients with AMI (four women, eight men) underwent 2D echocardiography at initial presentation. 2D strain images were analyzed to measure longitudinal and radial strain. Global strain was calculated as the average longitudinal strain of the segments of two-, three-, and four-chamber views. Biplane ejection fraction was assessed using Simpson's biplane method. Results: Significant differences in radial strain (TC vs. AMI) were found in lateral (13.5 ± 10.1% vs. 25.1 ± 11.2%, P = 0.035), posterior (15.2 ± 14.5% vs. 51.4 ± 14.2%, P < 0.001), and inferior (17.9 ± 15.5% vs. 49.4 ± 16.9%, P = 0.002) segments. Longitudinal strain was significantly lower in TC in basal-inferior (−15.8 ± 9.2% vs. −22.7 ± 3.8%, P = 0.037), midinferior (−8.3 ± 9.2% vs. −16.8 ± 3.0%, P = 0.004), basal-posterior (−12.2 ± 9.4% vs. −21.6 ± 4.4%, P = 0.016), midposterior (−4.4 ± 8.0% vs. −15.4 ± 3.5%, P = 0.002), apical-posterior (2.3 ± 6.7% vs. −6.4 ± 10.1%, P = 0.023), and midlateral (−3.4 ± 6.9% vs. −9.5 ± 5.8%, P = 0.028) segments. Global strain and ejection fraction were significantly higher in patients with AMI (−3.5 ± 8.2% vs. −10.3 ± 8.4%, P < 0.001 and 37 ± 11% vs. 46 ± 11%, P = 0.045). Conclusion: In TC, strain was reduced around the entire mid left-ventricular circumference, whereas in AMI it was predominantly reduced in the anterior and anteroseptal wall. These observed differences confirm the notion that TC affects myocardium beyond the territory of a single coronary artery. They may allow noninvasive distinction between both entities. (Echocardiography 2011;28:715-719)
First published: 04 May 2011
Gesehen am 28.09.2022